2019
DOI: 10.1039/c9ra01849b
|View full text |Cite
|
Sign up to set email alerts
|

What will happen when thermoresponsive poly(N-isopropylacrylamide) is tethered on poly(ionic liquid)s?

Abstract: A thermoresponsive ionic liquid diblock copolymer shows abnormal thermoresponse, and its aqueous solution remains transparent at the phase transition temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Luo et al studied a series of block copolymers P43a–f comprised of PNIPAM and styrene-based poly(vinylbenzyl)methylimidazolium (PVBMIm) with BF 4 − counterions. 127 As shown in Fig. 15B, copolymers with long cationic blocks are soluble at all temperatures.…”
Section: Thermoresponsive Cationic Copolymersmentioning
confidence: 84%
“…Luo et al studied a series of block copolymers P43a–f comprised of PNIPAM and styrene-based poly(vinylbenzyl)methylimidazolium (PVBMIm) with BF 4 − counterions. 127 As shown in Fig. 15B, copolymers with long cationic blocks are soluble at all temperatures.…”
Section: Thermoresponsive Cationic Copolymersmentioning
confidence: 84%
“…66–68 All the intensity of each peak decreases upon increasing the temperature, which seems to suggest that their protons are wrapped due to aggregation after phase transition. 69,70…”
Section: Resultsmentioning
confidence: 99%
“…The LCST-type behavior also vanished, as increase in P[VBMI][BF4] molar fraction resulted in less percent transmittance change. 93 Furthermore, in another example, introducing hydrophilic OEGMA300 and hydrophobic butyl methacrylate (BuMA) monomers to thermoresponsive poly(diethylene glycol methacrylate) (PDEGMA) to alter their cloud point temperature. It was shown that the cloud point increased when the content of OEGMA300 increased due to the hydrophilic effect, and the cloud point decreased as the amount of BuMA in the polymer increased due to its hydrophobicity.…”
Section: Copolymerization Of Different Componentsmentioning
confidence: 99%